Integrating entertainment and critical pedagogy for multicultural pre-service teachers: film watching during the lecture hours of higher education - Lee, Seung Chun (Taylor & Francis Group, 2019)
This article discusses the pedagogical opportunities to use film as a tool to supplement lecture and classroom learning activities in a pre-service teachers’ course in a Malaysian higher education setting. While the multicultural participants participated in two academic courses to learn how to teach spoken English to young learners, movie segments were usually introduced in the middle of lecture periods before the lecturer moved to another topic. Movie watching was connected to follow-up activities such as classroom discussion, and later in the second course, dramatic dialogue practices. Results indicated that film watching was effective in providing students with a healthy outlet for boredom or stress and refreshing moments to recharge their attention span. Furthermore, film watching was perceived as effective in promoting critical thinking and intercultural competence, resulting in attitudinal growth regarding openness to other cultures and different people. This study encourages the use of films during lecture periods to make the academic learning process fun and to provide significant opportunities to promote learners’ intercultural competence and expand their perspective of multiple educational and social issues, which is the essence of critical pedagogy.